Investigation of Science Teacher Candidates' Perceptions of Digital Material Design Competencies Across Four Core Dimensions - Yüzüak, Ahmet Volkan; Ocal, Zekiye Merve; Higde, Emrah (Univ Sultan Ageng Tirtayasa, Fac Teacher Training & Education (Fkip), Dse, 2025)
The study used both quantitative and qualitative techniques to examine how science teacher candidates perceived their capacity to create digital teaching resources. The 31-item Digital Material Design Competency Scale (DMDCS), a 5-point Likert scale with four sub-dimensions (design competence, technical competence, techno-pedagogical competence, and implementation-evaluation competence), was used in the embedded approach study to obtain quantitative data. Its reliability was reported as r =.72 from the previous study. Twelve science teacher candidates made up of the study group of this research. They took part in a ten-week intervention in which they had to develop six different kinds of digital materials which consist of games, quizzes, tales, animations, posters, and concept cartoons. To assess changes in self-perceived competence, the DMDCS was given as a pre-test and a post-test. The Wilcoxon Matched-Pair Signed-Rank Test results showed statistically significant improvements in each of the four competency domains, representing the beneficial intervention process. Complementary insights were found in the qualitative results, such as difficulties with English-language interfaces, limitations on paid platforms, data loss, and a lack of knowledge about ethical and digital security problems. These results clearly address the research questions by showing that the intervention enhanced the science teacher candidates' abilities to develop digital materials and changed their perspectives on utilizing digital technologies. Considering these findings, the study highlights the need for improving teacher education programs with structured, hands-on digital design experiences that also integrate digital ethics, privacy, and security awareness.
Keywords: Digital material design competency; Techno-pedagogical competence; Digital content creation